1998
DOI: 10.1001/archneur.55.4.530
|View full text |Cite
|
Sign up to set email alerts
|

Platelet Activation in Alzheimer Disease

Abstract: Platelets of patients with AD exhibit greater unstimulated activation than those of controls. Potential causes of such activation include possible stimulation of platelets by damaged cerebral endothelial cells or platelet activation induced by membrane abnormalities previously reported to be present in platelets of patients with AD. In light of recent evidence that platelets are the principal source of both amyloid precursor protein and beta-amyloid peptide in human blood, it is possible that AD platelet activ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
113
0

Year Published

1998
1998
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 164 publications
(118 citation statements)
references
References 42 publications
5
113
0
Order By: Relevance
“…47 Interestingly, it has been reported that AD patients have similar platelet counts as age-matched controls, but their platelets are in a more activated state. 48,49 Whether APP/ sAPPs are responsible for the phenotype in our patient cohort is unknown.…”
Section: Org Frommentioning
confidence: 99%
“…47 Interestingly, it has been reported that AD patients have similar platelet counts as age-matched controls, but their platelets are in a more activated state. 48,49 Whether APP/ sAPPs are responsible for the phenotype in our patient cohort is unknown.…”
Section: Org Frommentioning
confidence: 99%
“…Other case-control studies did not find significant differences in the levels of fibrinogen between patients with vascular dementia or Alzheimer disease and controls. 19,20 To our knowledge, the association of fibrinogen and vascular dementia and Alzheimer disease has not been studied in a large, prospective population-based setting.…”
Section: Van Oijen Et Al Fibrinogen Is Associated With Risk Of Dementmentioning
confidence: 99%
“…1 There is limited case-control evidence associating markers of hemostasis and inflammation with dementia. [2][3][4][5][6] Limited prospective data come from the Rotterdam Study, which found that fibrinogen, but not C-reactive protein (CRP), was associated with incident dementia at the age of 6 years. 7 Therefore, further studies of hemostatic and inflammatory markers and risk of dementia (both vascular and nonvascular) are required.…”
mentioning
confidence: 99%